ʼRaktakarabīʼra lokāẏata bhābanā - Sarakāra, Dīnendrakumāra (Loka Laukika Prakāśanī : paribeśaka, Pustaka Bipaṇi, 1983)
Study of the social and folk elements, in Raktakarabī, a play by Rabindranath Tagore, 1861-1941.